Key circular RNAs identified in male osteoporosis patients by whole transcriptome sequencing - Haijin Zhang; Xue Song; Zongyan Teng; Sujun Cheng; Weigang Yu; Xiaoyi Yao; Zhiqiang Song; Yina Zhang (PeerJ, 2021)
Background Osteoporosis (OP) is a systemic disease with bone loss and microstructural deterioration. Numerous noncoding RNAs (ncRNAs) have been proved to participate in various diseases, especially circular RNAs (circRNAs). However, the expression profile and mechanisms underlying circRNAs in male osteoporosis have not yet been explored. Methods The whole transcriptome expression profile and differences in mRNAs, circRNAs, and microRNAs (miRNAs) were investigated in peripheral blood samples of patients with osteoporosis and healthy controls consisting of males ≥ 60-years-old. Results A total of 398 circRNAs, 51 miRNAs, and 642 mRNAs were significantly and differentially expressed in osteoporosis compared to healthy controls. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that the host genes of significantly differentially expressed circRNAs were mainly enriched in the regulation of cell cycle process: biological process (BP), organelle part cellular components (CC), protein binding molecular function (MF), Toll-like receptor signaling pathway, tumor necrosis factor (TNF) signaling pathway, and thyroid hormone signaling pathway. circRNA-miRNA-mRNA regulatory network was constructed using the differentially expressed RNAs. Moreover, key circRNAs (hsa_circ_0042409) in osteoporosis were discovered and validated by qPCR. Conclusions The key cicrRNAs plays a major role in the pathogenesis of osteoporosis and could be used as potential biomarkers or targets in the diagnosis and treatment of osteoporosis.